The Relation of the Local and the Stranger in the Context of Multiculturalism - Avetisyan, Ghazar (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
In contemporary global processes migrations and intercultural mutual penetrations as well as the emergence of cultural collages and hybrids stand out with their influence. Due to incompatibility, and the impossibility of ideal harmony of human freedom and security, the contemporary man is in the process of constant identity creation. In this context expressions such as “Loss of roots”, “Rejection of one’s roots” etc. was replaced by the allegory of “Dropping and raising the anchor”. As a result of dropping and raising anchors, humans can end up in various cultural environments. This phenomenon has brought forth the idea of multiculturalism, which can become reality only thanks to tolerance and general “agreement”.